Chronostratigraphy of the Vistulian Glaciation (Weichselian) on the Kujawy Moraine Plateau (Central Poland) Based on Lithostratigraphic Research and OSL Dating - Przegiętka, Krzysztof; Chruścińska, Alicja; Oczkowski, Hubert Lucjan; Molewski, Paweł (Versita, 2008)
The subject of the investigations presented here is fixing dilemmatic character (transgressive or recessive) of the Poznań phase of the Vistulian (Weichselian) Glaciation and answering the question about the possibility of lithostratigraphic separation of this phase from the Leszno phase in the region of so called Vistula lob. Here we present the outcomes of the research project carried out on a few tills exposures, which constitute the sedimentological record of the last ice sheet advance on the Kujawy Moraine Plateau. The absolute ages of 17 samples (collected from fluvial deposits uncovered in the geological logs) have been determined by means of the OSL method applying the single aliquots regenerative (SAR) dose protocol. The OSL data are analysed with regard to supposed bleaching conditions at the moment of the last transport and deposition of the material. In conclusion, some remarks on suitability of fluvial sands for OSL dating are made. In most of the investigated sites, there appears to exist only a single till level associated with the main stage of the Vistulian Glaciation. This fact and the results of OSL dating support the hypothesis, that the Poznań phase in Kujawy Moraine Plateau is not a distinct lithostratigraphic unit, but it is a recessive phase of the last glaciation.